Simulation of directional crack propagation by energy-absorbing blasting in deep gob-side entry retaining under different lateral pressure coefficients - Nan Liu; Chuanqing Guo; Sudong Bao; Tao Wang; Feng Zhang; Zhongcheng Qin (PLoS ONE, 2026)
To address the challenges associated with directional roof-cutting through energy-absorbing blasting under high-stress conditions in deep gob-side entry retaining, this study combines numerical simulations and field tests to investigate the effects of varying lateral pressure coefficients (k) on crack propagation. Numerical simulations, utilizing an HJC constitutive model and an element erosion criterion, demonstrate that: (1) a higher lateral pressure coefficient significantly inhibits crack propagation, resulting in a reduction of main crack length and a simplification of crack morphology, while simultaneously increasing the proportion of elastic vibration energy; (2) optimal crack control is achieved when the energy-absorbing direction aligns with the maximum in-situ principal stress direction. The on-site verification at the 13303 working face demonstrates that aligning the opening of the energy-concentrating pipe with the direction of the roadway, which corresponds to the direction of the maximum principal stress, results in a directional main fracture occurrence rate exceeding 95%. significantly enhancing the retained roadway’s quality. These findings provide a theoretical foundation for precise blasting design in deep high-stress mining environments.